Uso de material reciclable, en las prácticas de laboratorio de ciencias naturales de la Universidad Técnica de Cotopaxi en la carrera de educación básica, ciclo académico marzo 2011- septiembre 2011 - Pacheco Calvopiña, Elisa Susana (2015)
This research involves the development and implementation of a guide on about the use of recyclable materials in the science lab. This intends to motivate teachers about the importance of implementing a science lab at the Technical University of Cotopaxi, thus improving teaching-learning process through practical classes and not only theoretical. This study was performed through a research into the institution mentioned previously. It was done by using the deductive method that goes from the general to the particular. This aims to discover the importance of recycling and the care of our mother nature since many people do not realize the damage they do by throwing plastic bottles and plastic bags....